A 16-year-old patient with 46,X,ider(X)(q28)i(X)(q10) chromosomal abnormalities diagnosed with premature ovarian insufficiency - Jong Chul Baek; Hyen Chul Jo; Seon Mi Lee; Ji Eun Park; In Ae Cho (IMR Press, 2021)
Background: Premature ovarian insufficiency (POI) is defined as the onset of a menopausal state prior to 40 years of age. Of the various causes of POI, genetic abnormalities account for 10.8% of all cases, which can be categorized into either chromosomal or gene anomalies. Chromosomal abnormalities of the isochromosome Xq [i(Xq)] type have been recognized as common causes of POI. Cases: A 16-year-old female presented with secondary amenorrhea that had persisted for one year. Her physical examination was unremarkable, including a height of 158 cm and the presence of secondary sexual characteristics. Her serum level of follicle-stimulating hormone was elevated (66 mIU/mL), whereas her estradiol and anti-Müllerian hormone levels were decreased (<10 pg/mL and 0.02 pg/mL, respectively). Conventional cytogenetic analyses of a peripheral blood sample showed the karyotype of 46,X,ider(X)(q28)i(X)(q10). Conclusions: We describe a novel chromosomal structural abnormality of the i(Xq) type that is associated with a diagnosis of POI.